Strategi Pemasaran Perusahaan Furniture CV. Orcard Collection Dalam Mempertahankan Usaha Furniture Pada Masa Peralihan Pandemi Ke Endemi Covid-19 - Melen Fitria Senna Ayrdelan; Erlita Ridanasti (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Building an existence in the furniture industry, CV Orcard Collection, a company that focuses on the production of wooden and rattan furniture, has faced various challenges in following the fast-changing market dynamics. Thus, there is a need for an in-depth analysis of the marketing strategies implemented by CV Orchard Collection in order to maintain and increase market share. Therefore, this research was conducted with the aim of analyzing the marketing strategy through Segmentation, Targeting, and Positioning (STP) applied by CV Orcard Collection and analyzing the 7P marketing mix elements (Product, Price, Place, Promotion, People, Process, and Physical Evidence) used by CV Orchard Collection in maintaining the furniture business during the transition from pandemic to Covid-19 endemic. The results of the STP analysis show that CV Orcard Collection has succeeded in identifying relevant market segments and determining the right target market, as well as positioning itself as a provider of wood and rattan furniture products with superior quality. In the context of the 7P marketing elements, the company has considered aspects such as product quality, appropriate pricing, effective distribution strategies, appropriate promotion, and attention to customer service and production processes. The conclusion from the analysis is that CV Orcard Collection has implemented an effective marketing strategy with the STP approach, focusing on market segmentation based on geographic, and psychographic consumers. By targeting property business owners and business people, and positioning itself through the tagline "3T", the company has succeeded in maintaining business sustainability. In the context of the 7Ps, CV Orcard Collection highlights its superior products, sets prices with a customized formula, and utilizes strategic physical locations, promotional efforts are focused on digital marketing, building positive relationships with consumers, ensuring production processes according to the tagline and maintaining a reputation as a high-quality furniture manufacturer. Therefore, this research can be a constructive suggestion for CV Orcard Collection to continue to update market segmentation and diversify target markets, maintain product quality consistency, and utilize local distribution and online platforms, while increasing visibility through social media, customer service, and production process efficiency, and strengthening branding and supporting facilities to improve consumer perception and company competitiveness.